1983
DOI: 10.1007/bf00286643
|View full text |Cite
|
Sign up to set email alerts
|

A deficiency mutant of the Gc system

Abstract: In the course of a paternity investigation an apparent mother-child incompatibility was observed in the Gc system. An extensive family study was undertaken to test the hypothesis of a silent gene or null allele responsible for the contrary phenotypes: the mother had the type Gc 2, the son was GC 1. The apparent incompatibility was due to a "pseudo" silent allele, called Gc * 1, which controlled a group-specific component with extremely reduced serum concentrations. This double-band mutant could be differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Polesky et al [1983] deter mined the Gc phenotypes in 8,100 motherchild pairs and 5,950 father-child pairs by IEF and no incompatibilities were found. Only a few other cases of incompatibility in the Gc system have been reported ear lier [Vavrusa et al, 1983]. Some of them have been explained by the presence of a silent allele and some of them, as ours, are still unexplained.…”
Section: Discussionmentioning
confidence: 92%
“…Polesky et al [1983] deter mined the Gc phenotypes in 8,100 motherchild pairs and 5,950 father-child pairs by IEF and no incompatibilities were found. Only a few other cases of incompatibility in the Gc system have been reported ear lier [Vavrusa et al, 1983]. Some of them have been explained by the presence of a silent allele and some of them, as ours, are still unexplained.…”
Section: Discussionmentioning
confidence: 92%
“…We mention also the deficiency mutant due the allele GC*le [Vavrusa et al, 1983], as well as the instances of a possible 'silent' gene which were observed by several investigators [Prokop and Rackwitz, 1968; The nomenclature adopted at the international work shop on the GC system held in July 1978 was used [Constans et al, 1979]. Double-band variants are called GC 1 and single-band variants are called GC2.…”
Section: Gc2 Variantsmentioning
confidence: 99%
“…In addition to the three common GC alleles, a total of 124 GC mutants have been identified. Furthermore, one deficien cy mutant has been recognized as well as several cases in which the existence of a silent gene GC*0 has been con sidered [for discussion, see Vavrusa et al, 1983], The polymorphic system, known since 1959 as groupspecific component (GC) [Hirschfeld, 1959], was identi fied by Daiger et al [1975] as the vitamin-D-binding protein (DBP) of human plasma. DBP has been demon strated in several mammalian species and has also been shown in fishes.…”
Section: Introductionmentioning
confidence: 99%
“…Vavrusa et al [10] described an aberrant Gc mutant Gc* 16 which produced an ab normal protein having normal binding ca pacity for vitamin D with a significantly decreased level in plasma. They were able to demonstrate a trace amount of the pro duct of the aberrant gene Gc* 10 using the two-dimensional technique developed by Constans [12], while in this case no appar ent product like Gc 16 was detected.…”
Section: Resultsmentioning
confidence: 99%
“…Several examples of adverse homozygosity in the Gc system have been reported, which may have different backgrounds, viz. hemizygosity at the Gc locus due to a deletion of the segment 4q 11 -q 13 on the long arm of chromosome 4 [4,5] or a marked reduc tion of the Gc level in plasma without any chromosomal abnormality [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%